Perfil sanitário de rebanhos ovinos criados na microrregião de Araçatuba- São Paulo, Brasil - Oliveira, Gabriela de [UNESP] (2015)
Recent years have seen a growing interest in sheep for meat production, mainly in São Paulo Northwest. In order to achieve greater productivity, greater food security and decreased expenditures and stemmed losses of diseases it is essential to recognize these problems, so that we can trace combat strategies of these, in addition to establishing preventive measures, so that you can reduce economic losses, maximize profits and provide a safe food. Through detailed analysis of questionnaires, direct observation in properties and sampling was done to characterize the sheep flock of micro-Araçatuba-SP, which is composed of seven municipalities. The animals were submitted to clinical and general examination by history, inspection and palpation, appropriate notes being made for the conditions of health, reproductive and nutritional management of these animals in their properties. During the visits to the properties they were made fecal collection of the rectum for monitoring by counting eggs per gram. Also punctures were performed nodules, when detected palpation for microbial culture. RESULTS: A lymphadenitis 50% history of properties, but was found in only 8.3% of these. Got an association between lymphadenitis history and mortality (p = 0.0693). It was found a history of foot problems in 91.6% of the properties was observed in 50% of them. It was found that foot problems and conducting foot baths are related (p = 0.0455). A mastitis history was obtained in 41.6% of properties, which was observed in 25% of them. About contagious ecthyma, it was reported by 25% of the properties, however, was not observed during the physical examination. The properties in its entirety declared conduct immunization against clostridial diseases. 25% had other types of vaccines. In 91.6% of the properties animals were observed with symptoms of worms. The Fisher exact test showed association between mortality...(complete abstract, electronic access below)